INTERMATHEMATIC POSSIBILITIES: IOC, PLANE OF IMMANENCE AND THE ARCHITECTURE OF THE CONCEPTS - Juliano Bona; Camila Thaisa Alves Bona; José Marcelo Freitas de Luna (Universidade Federal de Sergipe, 2019)
When we think of mathematics we feel we are facing a kind of universal knowledge that brings us closer to the truth. Transcendence is the space where we place this kind of objectification of mathematics. However, criticism of this type of hegemonic mathematics has been growing in recent years. In the face of hegemony and criticism, the objective of this article is to analyze internationalization of the curriculum (IoC) as the plane of immanence, and the process of conceptual construction in the field of philosophy. On these bases which in some ways represent the background that supports the critique of hegemonic mathematics, we can think of other possibilities that we call intermathematics. As an essay text, it follows theoretical contribution: BACHELARD (2008), BICUDO (1993), CANDAU (2002), DELEUZE (2000), DELEUZE (1996), FOUCAULT (2013), LEASK (20015), LUNA (2016), SANTOS (2002), SILVA (2010). To achieve the general objective, we divide the analysis into three parts. First, we approach the relationship between IoC and the immanence plan in the field of mathematics education. In a second moment, we discuss the idea of the plane of immanence and the IoC. Finally, we articulate methodological aspects, the plane of immanence and the conceptual construction process in an attempt to construct intermathematic possibilities. In this movement, we emphasize not only criticism of hegemonic mathematics, but also we indicate the ways of thinking mathematics in immanence through geo-mathematics, ethnomathematics and intermathematics.